2018
DOI: 10.1248/bpb.b18-00165
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Amino Acids across the Vacuolar Membrane of Yeast: Its Mechanism and Physiological Role

Abstract: In yeast cells growing under nutrient-rich condition approximately 50% of total amino acids are accumulated in the vacuoles; however, the composition of amino acids in the cytosol and in the vacuoles is quite different. The vacuoles, like lysosomes, degrade proteins transported into their lumen and produce amino acids. These amino acids should be quickly excreted to the cytosol under nutrient starvation condition and recycled for de novo protein synthesis. These suggest that specific machineries that transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…USPase is the major enzyme responsible for the synthesis of raffinose family oligosaccharides, which can protect plant cells during seed desiccation and drought stress [76]. Moreover, B. hygrometrica AVT1L encodes a homolog of yeast AVT, which is also hypomethylated and up-regulated in rapid desiccation-tolerant plants subjected to dehydration stress (S12 Fig) . This homolog is reportedly involved in the transport of large neutral amino acids including glutamine (asparagine), isoleucine (leucine), and tyrosine into vacuoles, thus maintaining the homeostasis of vacuolar and cytosolic amino acids [77]. Therefore, we hypothesized that drought stress-induced hypomethylation and upregulation of memory genes associated with alternative splicing changes and accumulation of oligosaccharides and vacuolar amino acids, allow rapid adjustment of the abundance and function of key stressresponse components, which ultimately contribute to the improvement of dehydration tolerance in B. hygrometrica.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…USPase is the major enzyme responsible for the synthesis of raffinose family oligosaccharides, which can protect plant cells during seed desiccation and drought stress [76]. Moreover, B. hygrometrica AVT1L encodes a homolog of yeast AVT, which is also hypomethylated and up-regulated in rapid desiccation-tolerant plants subjected to dehydration stress (S12 Fig) . This homolog is reportedly involved in the transport of large neutral amino acids including glutamine (asparagine), isoleucine (leucine), and tyrosine into vacuoles, thus maintaining the homeostasis of vacuolar and cytosolic amino acids [77]. Therefore, we hypothesized that drought stress-induced hypomethylation and upregulation of memory genes associated with alternative splicing changes and accumulation of oligosaccharides and vacuolar amino acids, allow rapid adjustment of the abundance and function of key stressresponse components, which ultimately contribute to the improvement of dehydration tolerance in B. hygrometrica.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…It is interesting that the peptide (KFF)3K within 15 min or less caused changes in the vacuole, which is a cytoplasmic organoid. Decrease in vacuole electron density (Figure 5A) compared to intact cells (Figure 2) suggests a disturbance of ion transport through the vacuole membrane and the flow of water into the vacuole cavity, the membrane of which carries numerous transport channels [49,50,[55][56][57][58].…”
Section: Impact Of R9f2 and (Kff)3k Peptides On C Albicans Cell Ultrastructurementioning
confidence: 99%
“…1,2) Amino acids obtained by protein degradation are transported from the lysosome/vacuole to the cytosol and recycled for protein synthesis. 3) Recent studies revealed that autophagy selectively degrades various materials, for example, organelles such as mitochondria and the endoplasmic reticulum, along with protein aggregates, phase-separated droplets, and even invasive microbes, thereby contributing to cellular homeostasis. [4][5][6] Pioneering studies using budding yeast identified two ubiquitin-like modification systems named the Atg8 system and the Atg12 system, which are evolutionarily conserved in higher eukaryotes (including mammals and plants) and essential for autophagy.…”
Section: Introductionmentioning
confidence: 99%